The role of the Amyloid Precursor Protein mutations and PERKdependent signaling pathways in the pathogenesis of Alzheimer’s disease - Rozpędek, Wioletta; Nowak, Alicja; Pytel, Dariusz; Lewko, Dawid; Diehl, J. Alan; Majsterek, Ireneusz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2016)
Alzheimer’s disease (AD) is a highly complex, progressive, age-related neurodegenerative human disease entity. The genetic basis of AD is strictly connected with occurrence of mutations in Amyloid Precursor (APP) gene on chromosome 21. Molecular mechanism that leads to AD development still remains unclear. Recent data reported that it is closely correlated with Endoplasmic Reticulum (ER) stress conditions, which subsequently activate Unfolded Protein Response (UPR) signaling pathways, via the induction of protein kinase RNA-like endoplasmic reticulum kinase (PERK), as a self-protective, adaptive response to adverse stress conditions. That results in the attenuation of global protein synthesis and, on the contrary, selective translation of Activating Transcriptor Factor 4 (ATF4) and secretase β. Interestingly, under prolonged, severe ER stress UPR may switch its signal into apoptotic cell death. That ensues by ATF4-CHOP-mediated activation of a range of pro-apoptotic genes and, on the other hand, downregulation of the expression of the anti-apoptotic protein B-cell lymphoma 2 (Bcl-2) genes. Current investigations suggest that inhibitions of PERK activity may contribute to the attenuation of the deposition of toxic senile plaques in the brain tissue and, as a result, prevent degeneration of neurons and decline in cognitive abilities.